Phase transformation in mechanically alloyed and hot-pressed Ti-2Nb- 22Si-11B and Ti-6Nb-22Si-11B powder mixtures - Zanardo, Andrezza Campos [UNESP]; Mariano, Neide Aparecida [UNESP]; Alkmin, Luciano Braga; Da Silva Costa, Matos Alex; Nunes, Carlos Angelo; Ramos, Alfeu Saraiva [UNESP] (Trans Tech Publications, 2014)
This work aims to discuss on the phase transformation in mechanically alloyed and hotpressed Ti-2Nb-22Si-11B and Ti-6Nb-22Si-11B powder mixtures. The milling process was conducted in a planetary ball milling using stainless steel vials (225 mL) and balls (19 mm diameter), rotary speed of 300 rpm, and a ball-to-powder weight ratio of 10:1. Hot pressing of mechanically alloyed Ti-Nb-Si-B powders was performed under vacuum at 1100oC for 1h. The asmilled and hot-pressed Ti-Nb-Si-B samples were evaluated by X-ray diffraction, scanning electron microscopy, and energy dispersive spectrometry. XRD results of milled Ti-Nb-Si-B powders indicated that the peaks of Nb and Si were reduced for longer milling times, suggesting that Nb and Si atoms were dissolved into the Ti lattice to form extended solid solutions. Iron contamination close to 6 at% was detected by EDS analysis. Hot pressing produced dense and homogeneous samples containing a small amount of Ti6Si2B.
Keywords: Mechanical alloying; Phase transformation; Titanium alloy